Estimating Computational Thinking Ability Using Tablets and Electronic Pens - Urayama, Kohei; Shimakawa, Hiromitsu (Advances in Social Sciences Research Journal, 2024)
This study proposes a method to estimate a computational thinking ability utilizing handwritten logs. The development of computational thinking skills to build a plan to organize solutions is crucial from an early age. The methods for cultivating these abilities in elementary education are still in the developmental stages. The proposed method analyzes hand-drawing logs obtained through tablets and electronic pens. Participants are assigned illustration tasks utilizing the layer functionality. The transition among layers objectively assesses whether individuals solve tasks in a perspective manner according to a plan. In an experiment involving 24 students and graduate students, an application with seven layers is employed to assign a 20-minute task of replicating a car illustration. From the results, it turns out we can estimate computational thinking abilities from hand-drawing logs. In addition to that, the results reveal the characteristic way of using and holding the pen that occurs when one has a planning perspective unique to computational thinking. This research promotes the ongoing exploration of methodologies for assessing computational thinking skills, particularly in the context of elementary education. It contributes to fostering computational thinking abilities in younger ages.